2014
DOI: 10.1097/jto.0000000000000109
|View full text |Cite
|
Sign up to set email alerts
|

ALK/EML4 Fusion Gene May Be Found in Pure Squamous Carcinoma of the Lung

Abstract: ALK translocation may be found in lung pure squamous cell carcinomas. Our data suggest the opportunity to test ALK rearrangements on biopsy samples harboring squamous cell cancer differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…The data are also supported by other studies specifically reporting the frequency of 0% ALK translocation in SCC patients [23][24][25]. Since the current practice guidelines recommend a molecular testing for lung adenocarcinoma or mixed lung cancer with an ADC component to select patients for targeted TKI therapy, reported cases of lung squamous cancer harboring gene rearrangements challenge the molecular diagnosis based on histologic subtypes [12,15,[26][27][28][29][30]. However, doubts have been cast on reports showing ALK and/or ROS1 rearrangements in squamous lung cancer, as the small biopsy specimens were not representative of the whole tumor characteristics, and an immunohistochemistry panel was not available to validate the squamous differentiation.…”
Section: Introductionmentioning
confidence: 49%
“…The data are also supported by other studies specifically reporting the frequency of 0% ALK translocation in SCC patients [23][24][25]. Since the current practice guidelines recommend a molecular testing for lung adenocarcinoma or mixed lung cancer with an ADC component to select patients for targeted TKI therapy, reported cases of lung squamous cancer harboring gene rearrangements challenge the molecular diagnosis based on histologic subtypes [12,15,[26][27][28][29][30]. However, doubts have been cast on reports showing ALK and/or ROS1 rearrangements in squamous lung cancer, as the small biopsy specimens were not representative of the whole tumor characteristics, and an immunohistochemistry panel was not available to validate the squamous differentiation.…”
Section: Introductionmentioning
confidence: 49%
“…Among the 209 patients with squamous cell carcinomas, 16 incidences (7.7%) of ALK rearrangement were detected, which is less than the incidence (11.0%) in adenocarcinoma, but not significantly so. Caliò et al (2014) also demonstrated ALK rearrangements in squamous lung cancers, as those might represent adenosquamous neoplasms misdiagnosed because of false squamous cell carcinomas, limited biopsy samples not representative of the entire lesion, and lack of use of an immunohistochemical confirmatory panel. However, the 16 patients with squamous carcinoma enrolled in our study comprised nine with whole-tissue from surgery, demonstrating that the ALK translocation might be found in pure squamous carcinoma of the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical characteristics should not be a limiting factor for exploratory analyses, and testing should be particularly encouraged in the case of never/light smokers [28]. ALK abnormalities in epidermoid lung cancers are extremely rare (one (0.2%) out of 523) [28], and the few studies reporting higher incidences should not, at this stage, change the above recommendations about screening [29].…”
Section: Characteristics Of Alk + Populationsmentioning
confidence: 99%